COLOMBIAN'S COAL SPATIAL PRODUCTIVE CIRCUIT: HOW COMMODITIES RE SHAPE THE DEVELOPMENT POLICIES (Encontros Universitários da UFC, 2022)
Colombia is a Latin American country considered upper middle income by the World Bank, with an approximate population of 50,911,747 and a gross domestic product (GDP) of 323.3 billion dollars. At the beginning of the 20th century, the international demand for coffee allowed its producing regions and articulated to the export economy, to develop an industry and infrastructure that configured an unequal regional development between the economic centrality and the other regions that persists to this day. As a consequence of the above, currently the central region made up of the cities of Bogotá, Medellín, Cali and their states produces 57% of the GDP, concentrating 45.11% of the national population, showing just a 18% of poverty. For its part, the Caribbean region divided into 7 states concentrates 21.73% of the population, and produces 14.4% of the GDP, with the highest poverty rate in the country of 42.38%. This article analyzes the causes that maintain the substantial levels of poverty in the Caribbean region, its stagnation in social mobility and its low productivity in a new context of regional division of labor focused on the mining industry, and debates on the role of agents, institutions and political practices that affect the processes of modernization and regional development. This problem poses a challenge for geographic studies in relation to the appropriate methodology to measure the spatial inequalities that continue to be present in social formations, especially in the global south but crosses various global, national, regional and local scales.